A participação da comunidade escolar em uma escola transformada em comunidade de aprendizagem - Caires, Sueli de Fatima Barbosa (2010)
This work aimed to characterize and analyze the ways of school community s participation in the daily routine of a school unity transformed into Learning Communities, in particular examining the participation in decision processes as a fundamental aspect of democratic management of education. We tried to understand the factors that facilitated or hindered participation in the context of the school studied. The proposed Learning Communities aims to transform social and cultural life of the school and its surroundings and is based on dialogic learning as a means to seek the highest quality education for everyone. Learning Communities is a proposal developed by the Special Centre for Research in Theories and Practices for Overcoming Inequalities (Centro Especial de Investigação em Teorias e Práticas Superadoras de Desigualdades CREA, in portuguese), of the University of Barcelona, has established in Spain as a successful experience. Today is being developed in several countries, including Brazil. The research was conducted at a school in the São Carlos urban periphery (SP), transformed into Learning Communities, based on some principles of Critical Communicative Methodology, which has references to the Paulo Freire s concept of dialogue, and the Jürgen Habermas theory of communicative action. The study was developed by quantitative data - a questionnaire administered by researchers inserted in the investigation into Learning Communities - and qualitative data - from interviews with managers of the school. Following the principles of critical communicative methodology, the process of data analysis was developed jointly between the participants and the researcher is talking about the content posted, the categories listed and understandings made, and coming to a consensus on the analysis dimensions of transformational and barriers to participation. We have observed that many changes occurred in the life of the school since the implementation of the proposed Learning Communities. Among them, egalitarian dialogue s reinforcement in relationships, which favored the school community participation in various spaces. We stress, however, the necessary support of management education as an indispensable element in creating and sustaining a school environment that stimulates democratic coexistence, because it does not occur spontaneously without intentional and permanent purposeful actions.